Assessing the impact of China’s river chief system on enterprise pollution discharge - Du, Jianxiao; Li, Bo (Frontiers in Public Health, 2023)
The River Chief System (RCS), an important environmental governance policy promoted by the Chinese government, also holds significant implications for public health. By controlling corporate pollution emissions, RCS has played a positive role in improving environmental quality and safeguarding people's health. This study utilizes the database of industrial enterprises and data from heavily polluting enterprises spanning the years 2003 to 2013. It also incorporates manual collation of RCS policy implementation across each prefecture-level city over the same period. The double-difference method is employed to verify the impact of RCS on the extent of corporate pollution emissions. The timeframe from 2003 to 2013 was selected for this study due to the occurrence of significant events and policy changes closely associated with environmental governance during this period. The study's findings indicate that (1) RCS significantly reduces the degree of pollution emissions from enterprises; (2) heterogeneity analysis shows RCS to be more effective in addressing visible pollutants in rivers, as well as in non-provincial capitals and heavily polluting industries, thereby leading to a reduction in pollution emissions; (3) the mechanism test reveals that increasing government attention to environmental protection and strengthening environmental regulation are key factors contributing to RCS's success in reducing pollution emissions from enterprises; (4) Additionally, improving the business environment of enterprises (measured through the marketization index) also enhances the effect of RCS on the improvement of river pollution by enterprises. In summary, this study provides a new perspective on examining the pollution reduction and abatement effects of RCS, bridging a gap in research at the micro-firm level. Furthermore, it offers valuable insights for governments and policymakers in promoting the further development and implementation of RCS policies, thereby contributing to the enhancement of public health. The results of this research hold great significance in strengthening environmental governance and safeguarding people's health.